2011
DOI: 10.1002/ejoc.201101335
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thiazoline–Oxazoline Ligands and Their Application in Asymmetric Catalysis

Abstract: A series of novel ligands incorporating oxazoline and thiazoline units were synthesized in high yield by employing a convergent route, in which the key step is a microwave-assisted palladium-catalyzed aryl amination. The new ligands were tested in the zinc-catalyzed Friedel-Crafts alkylation of indole with trans-β-nitrostyrene, inducing enantiomeric excess values of up to 69 %. The complete series of these ligands was also applied to the chromium-catalyzed Nozaki-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 90 publications
0
16
0
1
Order By: Relevance
“…Also, 2‐arylthiazoline framework is present in near‐infrared (NIR) light emitting bioluminophore 5 . Moreover, 2‐arylthiazolines are also employed as ligands in catalytic reactions Consequently, tremendous attention has been devoted to the development of efficient methodologies for the synthesis of such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Also, 2‐arylthiazoline framework is present in near‐infrared (NIR) light emitting bioluminophore 5 . Moreover, 2‐arylthiazolines are also employed as ligands in catalytic reactions Consequently, tremendous attention has been devoted to the development of efficient methodologies for the synthesis of such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the cinchona alkaloid family and its derivatives as the chiral amine parts of catalysts possessed high catalytic activity resulting in a high ee value in the asymmetric Michael addition . However, there are only a few examples that chiral thiazoline‐catalysts have been employed since they were first investigated by Helmchen et al in 1991 . There is no report about cinchonine‐ and quinine‐derived chiral thiazoline‐containing catalysts, although the imino moiety‐containing thiazoline is an efficient surrogate for the functional amino unit in some chiral catalysts.…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34][35][36][37] However, there are only a few examples that chiral thiazoline-catalysts have been employed since they were first investigated by Helmchen et al in 1991. [38][39][40][41][42][43] There is no report about cinchonine-and quinine-derived chiral thiazoline-containing catalysts, although the imino moietycontaining thiazoline is an efficient surrogate for the functional amino unit in some chiral catalysts. Therefore, the development of efficient new catalysts containing thiazoline for asymmetric transformations is challenging.…”
mentioning
confidence: 99%
“…Guiry and his research group develop new catalysts and synthetic methods to prepare biologically interesting compounds, particularly those with anti‐inflammatory properties. He has reported in ChemMedChem on lipoxin analogues,1a in the European Journal of Organic Chemistry on oxazoline ligands 1b…”
Section: Featured …︁mentioning
confidence: 99%